The Interplay Between Problem Gambling and Narcissism - Tochkov, Karin (Advances in Social Sciences Research Journal, 2024)
Problem gambling and narcissism represent two distinct yet interconnected psychological phenomena with significant implications for individuals and society. This paper seeks to explore the complex relationship between problem gambling and narcissism, shedding light on the psychological mechanisms, empirical evidence, and therapeutic implications. Through a comprehensive review of the literature, this research aims to deepen our understanding of how these constructs intersect and inform preventive and therapeutic interventions.